MicroRNA-31 Regulates Immunosuppression in Ang II (Angiotensin II)–induced Hypertension by Targeting Ppp6C (Protein Phosphatase 6c). Issue 5 (May 2019) - Li, Xiangxiao; Cai, Wei; Xi, Wenda; Sun, Weihong; Shen, Weili; Wei, Tong; Chen, Xiaohui; Sun, Libo; Zhou, Hong; Sun, Yang; Chen, Wendong; Gao, Pingjin; et al.
Abstract : Regulatory T cells (Treg cells) play important roles in hypertension and organ damages. MicroRNA-31 (miR-31) is a critical regulator for Treg cell generation. However, the role of miR-31 in hypertension has not been elucidated. We aim to study the functionality of miR-31 and the detailed mechanism in Ang II (Angiotensin II)–induced hypertensive mouse model. We found: In vitro, miR-31 expression was higher in T helper 17 cells and lower in Treg cells than that of naïve T cells. The genetic deficiency of miR-31 promoted Treg cell differentiation, whereas no impact on T helper 17 cells differentiation. Ang II–induced hypertension resulted in increased expression of miR-31 in the aorta, splenic CD4 + T cells, and kidney leukocytes. MiR-31 deficiency strikingly decreased systolic blood pressure and diastolic blood pressure and attenuated renal and vascular damage. MiR-31 deletion altered the accumulation of Treg cells and macrophages and expression of inflammatory cytokines in kidneys in Ang II–induced hypertensive mice. Ang II treatment reduced the levels of anti-inflammatory cytokines and increased proinflammatory cytokines in plasma that were blunted by the miR-31 deletion. Ppp6C (protein phosphatase 6c; a direct target of miR-31) specific deletion in Treg cells led to marked impairment of Treg cell induction, increased Ang II–induced blood pressure elevation, and organ damage in mice. In conclusion, we provided novel evidence of miR-31 as an emerging key posttranscriptional regulator of hypertension-associated immunosuppression through targeting ppp6C which is a critical regulator in the differentiation of Treg cells. This study offers new perspectives on miRNA-based therapeutic approaches. Abstract : Supplemental Digital Content is available in the text.